2019
DOI: 10.5125/jkaoms.2019.45.5.260
|View full text |Cite
|
Sign up to set email alerts
|

7-mm-long dental implants: retrospective clinical outcomes in medically compromised patients

Abstract: ObjectivesDental implants shorter than 8 mm, called short dental implants (SDIs), have been considered to have a lower success rate than standard length implants. But recent studies have shown that SDIs have a comparable success rate, and implant diameter was more important for implant survival than implant length. Also, SDIs have many advantages, such as no need for sinus lifting or vertical bone grafting, which may limit use in medically compromised patients.Materials and MethodsIn this study, 33 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…According to finite element analyses, the implant stress values were showed and application points showed lower for cortical bone with the implant diameter were increased [25]. Furthermore, the implant diameter more effectively reduced outer layer of bone strain with increased diameter, when comparing to the implant length when increasing (3.5-fold vs. 1.7-fold) [26].…”
Section: Discussionmentioning
confidence: 97%
“…According to finite element analyses, the implant stress values were showed and application points showed lower for cortical bone with the implant diameter were increased [25]. Furthermore, the implant diameter more effectively reduced outer layer of bone strain with increased diameter, when comparing to the implant length when increasing (3.5-fold vs. 1.7-fold) [26].…”
Section: Discussionmentioning
confidence: 97%
“…In our cases, we immediately installed an SDI in five patients, including two re-installation cases. Nguyen et al 46 reported a high survival rate of SDI in medically compromised patients and considered SDI as a reliable treatment in avoiding sinus lifting or vertical bone grafting. In a previous systematic review and meta-analysis, no significant differences in implant survival, marginal bone loss, complications, and prosthesis failure were found between SDI and standard dental implants in posterior jaws.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those of previous studies showing the clinical feasibility and the benefits of the tapered SLA implant under various clinical conditions, in medically compromised patients, and in poor quality bones. 16,17 To maintain peri-implant tissues in a healthy state and increase patient satisfaction, it is necessary to determine the optimal implant type considering locations of implant placement and surrounding conditions. In the present study, bone level and tissue level implants with internal connection were selectively used in consideration of characteristics of the disease and locations of implant placement.…”
Section: Discussionmentioning
confidence: 99%